A Cross-sectional Study of Nutritional Status and Cardiovascular Health Status among Housewives in Tegal Regency, Central Java (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Unhealthy diet and physical inactivity are two major factors related to degenerative diseases such as diabetes, hypertension, cancer, and it is still growing issues that mainly occurred in developing countries like Indonesia. It is a descriptive quantitative study, aims to investigate nutritional also cardiovascular health status among housewives in Tegal Regency, Central Java. Twenty adult women (33-57 years old) were voluntary and randomly signed up. Data on body weight (kg), height (cm), waist circumference (cm), hip circumference (cm), systolic-diastolic blood pressure (mm/hg) were collected by survey and measurement techniques. IBM SPSS 21 used to perform descriptive quantitative analysis for all data. Body mass index: 35% obese, 45% pre-obese, 5% overweight, 15% ideal weight. Waist circumference: 35% low category, 65% high category. Waist-to-hip ratio: 60% at risk of chronic diseases, 35% moderate, 5% good. Blood pressure: 40% hypertension stage-two, 25% hypertension stage-one, 25% elevated, 10% normal. Pre-obese and obese have found as the current nutritional status, followed by overweight. Meanwhile, hypertension has found as the current cardiovascular health status, followed by elevated blood pressure. This novel is empirical evidence for the housewife to be more physically active, and manage the diet to improve their health status.